Petty business - Pinkus, Yirmi, 1966- (Judaic traditions in literature, music, and art., 2017)
Winner of The Israel Institute's Literary Prize As they do every year, Yosef Zinman, a well-to-do Tel Aviv grocer, and his beloved wife Zippi plan a vacation during the holiday of Sukkot to Seefeld in the mountainous Tirols region of Austria. This year, Zippi decides to invite her sister, who has fallen on hard times with a failing perfumery business. Soon, more and more relatives join in on the trip, and the expenses quickly begin to add up. To gather all the funds needed, the family goes into the business of inexpensive clothing and fashion shows for workers' unions. The summer promises handsome revenues, but as the Zinman family nears their goal, they become increasingly vexed by their competing interests. A tragic-comic novel in its essence, Petty Business chronicles a year in one family's life, set against the backdrop of Tel Aviv's rapidly changing global economy in the early 1990s. Pinkus's biting critique of Tel Aviv's provincial character and its residents' shtetl mentality is delivered with a perfect combination of wit, humor, and tender pathos.